Diffuse characteristics and piezoelectric properties of Tb-doped BCZT ceramics with CaCl2 as sintering aid. Issue 18 (15th December 2017) - Lu, Haowei; Liu, Lizhu; Lin, Jiaqi; Yang, Wenlong; Zheng, Weijie; Weng, Ling; Zhang, Xiaorui
Abstract: Lead-free ceramics 47(Ba0.7 Ca0.3 )TiO3 –0.53Ba(Zr0.2 Ti0.8 )O3 (BCZT) + 0.2 mol% Tb and xCaCl2 (x = 0.1, 0.2 and 0.3 wt%) were prepared at different temperatures (1300, 1350 and 1410 ℃) by solid-state reaction method. The experimental results reveal that dopants can effectively promote the growth of grain at relatively low sintering temperature and CaCl2 as the well sintering aid can produce a pronounced liquid phase to fill the gap between grains sintered at 1410 ℃ with 0.2 wt%. Relative densities and piezoelectric properties of samples can be improved by the introduction of Tb and CaCl2 . Comparing with pure BCZT, the residual polarization ( P r ) and piezoelectric coefficient ( d 33 * ) of ceramics increase from 8.2 to 11.4 μC/cm 2 and 568–720 pm/V with 0.2 mol% Tb and 0.2 wt% CaCl2 doped. The enhanced properties of samples may be related to the appearance of liquid phase which can increase relative densities of ceramics to 96% and the form of defect dipole in ceramics. Moreover, introduction of CaCl2 makes dielectric peaks ( T c ) move to the high-temperature zone about 13 ℃ and become more and more diffuse (γ = 1.71–1.86), which may have the potential electro-caloric effect application in ferroelectrics.